Developing nationalism character-based children's literature module to increase Islamic elementary school students' critical thinking - Hajarudin Al Fikri (Prodi PGMI IAIN Salatiga, 2018)
This study aims at producing a literature module of children based on nationalism character to improve the critical thinking ability of fourth grade students MIN Boyolali, and measuring the effectiveness of the module use in classroom toward critical thinking ability of fourth grade students MIN Boyolali. Set within the research and development type, this study adapts 10 (ten) stages of development procedure as formulated by Borg and Gall (1983). The subjects of the research were students and teachers of grade IV MIN Boyolali. Data collection was conducted through interview and observation, product validation, teacher and student response questionnaire, and performance of pre-test and post-test—which was analyzed using independent sample t-test. Meanwhile, product effectiveness was tested through quasi experiment. The result of the research showed that the module was categorized as “fit” by material and language expert; while the media expert categorized it as